ChemInform Abstract: General Cycloaddition Between a Trimethylsilyl‐Capped Alkyne and an Azide Catalyzed by an N‐Heterocyclic Carbene‐Copper Complex and Pyridine‐Biscarboxamide. Issue 41 (September 2016) - Xu, Haochen; Sun, Zhihua
Abstract: The title reaction is applied to a variety of Tms‐capped substrates (I), with electron‐rich alkynes generally giving higher yields and nitroaromatic alkynes giving lower yields.